"Tengo Feuza en la Piyadad de Allāh": Piety and Polemic in an Aljamiado-Morisco "Companion in Paradise" Narrative. - Wood, Donald Walter (Medieval Encounters, 2020)
The subject of this study is the Aljamiado-Morisco narrative, the Alḥadix đe Musā kon Yako el-karniçero , found in Madrid, BNE, MS 5305; an adaptation of the popular "Companion in Paradise" folktale type. Through a comparative reading of this and similar renderings of this tale, I will demonstrate that the Aljamiado narrative develops a detailed exemplification of ritual-like domestic practices that, within a Morisco context of use, served as a model for the proper care of one's parents. For his fulfillment of these practices, the protagonist Jacob, condemned by the members of his community identified collectively as Banī Isrāʾīl, is promised a privileged place in Paradise alongside the prophet Moses. Contextualized within an Aljamiado-Morisco manuscript, Jacob's reward is reframed as a polemical victory for Islam over other monotheistic traditions; a recurrent theme linking several of the texts contained in this manuscript.